2017
DOI: 10.1016/j.celrep.2017.08.014
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Apela Peptide in Mice Causes Low Penetrance Embryonic Lethality and Defects in Early Mesodermal Derivatives

Abstract: SUMMARY Apela (also known as Elabela, Ende and Toddler) is a small signaling peptide that activates the G protein-coupled receptor Aplnr to stimulate cell migration during zebrafish gastrulation. Here, using CRISPR/Cas9 to generate a null, reporter-expressing allele, we study the role of Apela in the developing mouse embryo. We found that loss of Apela results in low penetrance cardiovascular defects that manifest after the onset of circulation. Three-dimensional micro computed tomography revealed a higher pen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
46
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 52 publications
2
46
0
Order By: Relevance
“…To fully understand the roles of ELA, the ELA knockout mouse is a useful tool. However, a recent study reveals that knockout of ELA leads to lethal cardiac defects in some ELA null embryos 49 . Thus, heterozygous ELA knockout C57BL/6 mice (ELA +/− ) were used to verify its functions in this work.…”
Section: Discussionmentioning
confidence: 99%
“…To fully understand the roles of ELA, the ELA knockout mouse is a useful tool. However, a recent study reveals that knockout of ELA leads to lethal cardiac defects in some ELA null embryos 49 . Thus, heterozygous ELA knockout C57BL/6 mice (ELA +/− ) were used to verify its functions in this work.…”
Section: Discussionmentioning
confidence: 99%
“…Several miRNAs, peptides, and proteins derived from the placenta were shown as potential biomarkers of preeclampsia, but valuable and safe therapeutic targets are still urgently needed. Interestingly, the apelin/Elabela/APLNR axis is a major player in the development, growth, and function of the vascular system, including the extensive angiogenesis necessary for placental growth as well as normal embryonic and fetal development . More specifically, Elabela is known to be a hormonal guide for angioblasts during angiogenesis .…”
Section: Emerging Potential Of the Apelinergic System For Treating Prmentioning
confidence: 99%
“…As the landscape of GPCRs and their ligands continues to expand, Elabela (Ela, also referred to as Apela, or Toddler) recently emerged as a second ligand for APLNR (APJ or Apelin Receptor) [1, 2], a GPCR that has widespread implications in development and disease. While the two new studies of Ela null mice [3, 4] provide insight into the previously observed differences between the developmental phenotypes of the Apelin ( Apln , first identified ligand for APLNR) and Aplnr null mice [5, 6], they raise additional questions as we continue to seek mechanistic insights and therapeutic implications of this pathway.…”
mentioning
confidence: 99%
“…The two new studies sought to determine the role of Ela through the generation and phenotyping of Ela null mice [3, 4]. In the first study from the Reversade group, mouse embryos lacking Ela were found to have up to 50% incidence of embryonic lethality, and presented with a host of defects that were contributed to improper establishment of the fetal-maternal circulation, such as under-developed yolk sac vasculature, impaired cardiac tube looping, defective chorio-allantoic fusion and compromised hematopoietic progenitor specification [4].…”
mentioning
confidence: 99%
See 1 more Smart Citation